Longitudinal evaluation of diastema closure in patients submitted to labial frenectomy in different phases of the mixed dentition: a historical cohort - Rafael, M. Pereira (2021)
There is a controversy in the literature concerning the indications for frenectomy to treat interincisal diastema. Aims and Objectives: The aim of this study was to evaluate the spontaneous closure of the interincisal diastema in patients submitted to upper labial frenectomy (ULF) during the mixed dentition. Materials and Methods: Records from patients treated between 2009 and 2014 in the course of Pediatric Dentistry Surgery at Fundecto-USP were evaluated to select those that were submitted to ULF during the mixed dentition using the Chelotti technique. Initial clinic characteristics and radiographic data related to the abnormal upper labial frenum were collected. The patients were called for a return visit to evaluate the diastema closure. The prevalence of children with diastema reduction after the frenectomy was determined by descriptive analysis. Logistic regression was used to evaluate the association between exposure factors and diastema reduction. Results: From 449 eligible records, 53 were selected and 25 were in a return visit. It was not possible to find association between the exposure factors and diastema closure. Conclusion: There is no relation between the time of surgery intervention and diastema closure. However, the intervention during the mixed dentition led to a partial diastema reduction in 80% of the cases.